Perancangan Sistem Kontrol Kestabilan Kapal Korvet Sigma Hassanudin-366 Menggunakan Pendekatan Linier Dan Nonlinier Dengan Gangguan Gelombang Air Laut Sea State 6 - Devina Puspita Sari (Politeknik Negeri Madura, 2016)
Many disaster due to the magnitude of disturbance sea waves behind a study on the stability control system rolling corvette warship KRI Hassanudin SIGMA-366. In this study a comparison between dynamics modeling warship approach Nomoto linear and nonlinear Hamamoto. Fuzzy logic control is used Takagi Sugeno. KLF have two inputs, error heading and yaw rate. External disturbances such as waves disturbances sea state six. With the wave disturbances, responce control rolling stability to longer than no disturbances . Response actual stabilization test and simulation rolingl with input heading 200 and 300 in according to the standards of IMO (International Maritime Organization). The results of the modeling system performance stability control ship when the sea state is given disturbance wave six conducted by Nomoto linear method is better than the nonlinear state space Hamamoto method. Maximum overshoot generated by a closed loop system with linear and nonlinear wave disturbances have met the criteria with a maximum system stability overshoot twice before returning to a steady state with a maximum of time 18 seconds.